Development of the Organic Food Market in Romania during the COVID-19 Pandemic: a Perspective on the Supply Chain - MIHAI STOICA (Global Economic Observer)
Organic food is seen as a less harmful alternative to conventional products, both in terms of personal benefits as well as environmental benefits. Therefore, because health became a major concern during the COVID-19 pandemic, green consumption was one of the alternatives through which people tried to take care of their health. Changes also occurred in the organizations involved in the organic food market, these being forced to adapt to the new market context. This paper aims to highlight the most relevant characteristics of the organic food market in Romania, in the context of the Covid pandemic, from the perspective of the supply chain participants. The research method used was the in-depth individual interview, conducted among specialists from organic certified companies. The research was conducted among producers, processors, distributors and retailers, to provide an integrative view on the researched topic. The results showed that the growing interest of consumers in recent years in leaning towards organic food has been accentuated by the Covid-19 pandemic. This trend was intensified by the "democratization" of organic products observed among general retailers, which determined the gap between the prices of organic food and similar conventional alternatives to be smaller. However, the Romanian organic food market is still a niche, characterized by a low level of education among consumers regarding green consumption and by the lack of involvement of institutions empowered in the development of this market. These realities also lead to a small number of organic certified processors, which is reflected in the significantly limited number of locally packaged organic products. Even though the COVID-19 pandemic has provided a significant and unexpected impetus, sustained efforts must still be made by stakeholders to develop this market segment.